Numerical simulation of the two-phase flow and pollutant concentration changes in an oxidation ditch: A computational fluid dynamics and activated sludge model 3 approach - Rongrong Miao; Han Cui; Yuzhen Shi; Baoxiu Guo; Yanqiong Chen; Zhengbo Yang; Chengbo Chang; Wanyue Xu (Desalination and Water Treatment)
In this study, a computational fluid dynamics (CFD) model integrated with activated sludge model 3 (ASM3), which is based on the tandem reactor model (tank-in-series (TIS) method), is proposed to simulate the oxygen mass transfer process and biochemical reaction process in an oxidation ditch. The simulation results are consistent with the quality of the effluent from the actual water plant. On the basis of the coupled model, the effects of aeration volume and bubble size distribution (BSD) on dissolved oxygen (DO) were simulated. The increase in bubble diameter led to a gradual decrease in the volumetric mass transfer coefficient in the aeration area, whereas the volumetric mass transfer coefficient in the nonaeration area did not change significantly. A reduction in the bubble diameter could improve the oxygen transfer efficiency and reduce energy consumption. Moreover, the removal efficiencies of chemical oxygen demand (COD), total nitrogen (TN), and ammonia nitrogen (NH3-N) differed under different aeration amounts. However, increasing the excess aeration amount did not significantly improve their removal effects, mainly constrained by the activated sludge microbial population and its related kinetic factors. The above results indicate that the CFD-ASM3 coupled model can effectively simulate the effects of the aeration amount on the dissolved oxygen content and effluent water quality during oxidation ditch operation.